2017
DOI: 10.3892/ol.2017.7367
|View full text |Cite
|
Sign up to set email alerts
|

Ang1/Tie2 induces cell proliferation and migration in human papillary thyroid carcinoma via the PI3K/AKT pathway

Abstract: Abstract. The angiopoietin 1 (Ang1)/angiopoietin receptor (Tie2) signaling pathway may have a notable role in the pathogenesis of inflammatory diseases. The abnormal expression of angiopoietin 1 and Tie2 has also been reported in various malignant tumors, including papillary thyroid carcinoma (PTC). However, the role and mechanism of the Ang1/Tie2 pathway in the progression of PTC remains unclear. Therefore, the aims of the present study were to clarify this. Significantly high expression levels of Ang1 and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…It is possible that tumor cells that metastasize into the liver stimulate Ang1 expression in their environment (hepatocytes), which is important for blood vessel formation and growth of the tumor. It has been recently reported in human papillary thyroid carcinoma that upregulation of Ang1-Tie2 signalling activates pathways that are involved in cancer cells survival, proliferation and metastasis [26]. Furthermore, in-vitro, knockdown of Ang1 expression decreased the proliferation and migration of breast cancer cells, and found that the Ang1 overexpression rescued proliferation and migration of these cancer cells [27].…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that tumor cells that metastasize into the liver stimulate Ang1 expression in their environment (hepatocytes), which is important for blood vessel formation and growth of the tumor. It has been recently reported in human papillary thyroid carcinoma that upregulation of Ang1-Tie2 signalling activates pathways that are involved in cancer cells survival, proliferation and metastasis [26]. Furthermore, in-vitro, knockdown of Ang1 expression decreased the proliferation and migration of breast cancer cells, and found that the Ang1 overexpression rescued proliferation and migration of these cancer cells [27].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, KEGG analysis showed that the DEGs were mainly concentrated in 16 signaling pathways, including the thyroid hormone signaling pathway, the PI3K-Akt signaling pathway, the AMPK signaling pathway, and the phosphatidylinositol signaling pathway. Both the PI3K-Akt signaling pathway and the AMPK signaling pathway have been shown to be involved in the development of thyroid carcinoma [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…32 Sema4D may upregulate HIF-1⍺ directly or via VEGF, which can enhance expression of HIF-1⍺. 48 Angiopoietin 1 (ANG1) plays a crucial role in the regulation of vasculogenesis and remodeling, 49 and promotes endothelial differentiation of embryonic stem cells (ESCs). 50 As ANG1 is upregulated by Sema4D stimulation, ANG1 probably also plays some role in promoting the endothelial differentiation of DPSCs.…”
Section: Discussionmentioning
confidence: 99%